DUTIES AND LEGAL RESPONSIBILITIES OF PHARMACISTS IN PHARMACEUTICAL - Ady Supryadi (Media Keadilan: Jurnal Ilmu Hukum, 2023)
Pharmacist as a professional health worker in the field of pharmacy services in carrying out its duties is based on the code of Ethics  as  a  moral  psychiatric profession  work.  But a  profession  code  of  ethics  is  sometimes not very  much noticed. Consequently, the hallmark of the noble profession of pharmacy as a provision  of  assistance  in  the  form  of  drug  services  oriented  to  community needs,  wear  off  and  tend  to  be  commercial  transactions  of  pharmaceutical products  that  are  business - oriented.  The  research  method  uses  a  normative juridical  approach  with  research  specifications  of  the  analytical  descriptive.Data  collection  is  conducted  through  the  inventory  and  study  of  primary, secondary, and tertiary legal materials which are then analyzed in a qualitative juridical. The duty and authority of the pharmacist in carrying out the work of the pharmacy is in the manufacture including the quality control of pharmaceutical preparations, securing, procurement, storage and distribution of drugs, drug management, medical treatment of Doctor's prescription, drug information services, and the development of medicines, medicinal  materials  and  traditional  medicines.  The  responsibility  of  the  pharmacist  in  the  drug  service prescribed  by  the Doctor  is  to  prioritize  the  needs  and  safety  of  patients.  The  overall  responsibility  of pharmacists in drug service is pharmaceutical care to improve the quality of patient life